Immunogenicity of Fractional Dose Inactivated Poliovirus Vaccine in India. Issue 2 (16th November 2021) - Ahmad, Mohammad; Verma, Harish; Deshpande, Jagadish; Kunwar, Abhishek; Bavdekar, Ashish; Mahantashetti, Niranjana S; Krishnamurthy, Balasundaram; Jain, Manish; Mathew, Mannancheril A; Pawar, Shailesh D; Sharma, Deepa K; Sethi, Raman; et al.
Abstract: Introduction: Following the withdrawal of Sabin type 2 from trivalent oral poliovirus vaccine (tOPV) in 2016, the introduction of ≥1 dose of inactivated poliovirus vaccine (IPV) in routine immunization was recommended, either as 1 full dose (0.5mL, intramuscular) or 2 fractional doses of IPV (fIPV—0.1mL, intradermal). India opted for fIPV. We conducted a comparative assessment of IPV and fIPV. Methods: This was a 4-arm, open-label, multicenter, randomized controlled trial. Infants were enrolled and vaccines administered according to the study design, and the blood was drawn at age 6, 14, and 18 weeks for neutralization testing against all 3 poliovirus types. Results: Study enrolled 799 infants. The seroconversion against type 2 poliovirus with 2 fIPV doses was 85.8% (95% confidence interval [CI]: 80.1%-90.0%) when administered at age 6 and 14 weeks, 77.0% (95% CI: 70.5-82.5) when given at age 10 and 14 weeks, compared to 67.9% (95% CI: 60.4-74.6) following 1 full-dose IPV at age 14 weeks. Conclusion: The study demonstrated the superiority of 2 fIPV doses over 1 full-dose IPV in India. Doses of fIPV given at 6 and 14 weeks were more immunogenic than those given at 10 and 14 weeks. Clinical Trial Registry of India (CTRI). Clinical trial registration number was CTRI/2017/02/007793.